Industrialización de la higuerilla en la producción de aceite de crudo. - Pacheco Pacheco, Henry Orfay (2019)
The advances in the industrial field that are presented nowadays have taken an unexpected turn with new technologies increased in the country, feeding the new generations with alternative and renewable energies, crops that are established with the new industries, that help the environment and to the population. One of the alternative crops that shows good prospects is the castor bean cultivation, which, due to its easy adaptation to different soil types, with unfavorable agro-ecological conditions, allows the exploitation of large tracts of land. For this reason, the purpose of this research was to carry out a study on the industrialization of the oilseed (castor) for processing and marketing in crude oil for industrial use, for which a market study was proposed in order to establish the demand and commercialization of crude oil from the castor bean seed. A field investigation was also carried out based on the application of surveys to 74 small farmers dedicated to the cultivation of this plant in the Chone canton, in accordance with the results to establish the technical viability of the project. Finally, a financial evaluation of the project was carried out, which concluded that the industrialization of the castor oil crude is feasible, since, according to the information obtained in the market studies, technical study and financial study, the data are acceptable and assert the viability of the project, since a VAN of $ 58.725,94 and an TIR of 15% were obtained, results that will be used for decision-making around its execution